Les « abominations ottomanes » dans le discours libéral féminin au Royaume-Uni, (1875-1896) : de la dénonciation au militantisme féministe - Stéphanie Prévost (Genre & Histoire)
The denunciation of ‘Ottoman abominations’ in the British Liberal female discourse (1875-1896), or the question of feminist agitation.‘Ottoman abominations’ were frequent headline news in the Victorian press, especially in Liberal newspapers and periodicals, in particular at the time of the ‘Bulgarian atrocities’ (1876) and the ‘Armenian massacres’ (1894-1896) mostly committed by Ottoman irregulars against Ottomans Christians. Whereas the Liberal press coverage of the ‘Bulgarian atrocities’ has received due attention – especially in the wake of David Harris’s Britain and the Bulgarian Horrors of 1876 (1939) –, that of the ‘Armenian massacres’ has been relatively neglected. Secondary literature has largely overlooked their coverage in the female press, to the notable exception of a chapter by Anne Summers in David Feldman and Jon Lawrence’s recent Structures and Transformations in Modern British History (Cambridge, CUP, 2011). And yet, Liberal women too, such as Millicent Fawcett, did join in the Liberal outcry against such ‘abominations’, both in 1876 and some twenty years later. However, the endorsement of the cause of Ottoman Christians, in particular of women, by British (Liberal) women is not simply a matter of political alignment to strengthen the hands of Liberal governments, or of support to sympathising husbands and agitators. Rather, that British Liberal women should care at all for other women in foreign, remote, fairly little known Ottoman provinces is striking in itself and should be looked into. As a matter of fact, by trying to answer the questions of who these British women who cared for their Bulgarian and Armenian ‘sisters’ were, what rhetorical strategies and channels they used and why they ultimately did so, this article will show that the campaign in favour of Ottoman Christian women was closely interwoven with their own struggle back at home for more rights.